Radiological factors associated with the severity of corticospinal tract dysfunctions for cervical spondylotic myelopathy: An analysis of the central motor conduction time and kinematic CT myelography. (December 2021) - Funaba, Masahiro; Imajo, Yasuaki; Suzuki, Hidenori; Nagao, Yuji; Sakamoto, Takuya; Nishida, Norihiro; Fujimoto, Kazuhiro; Sakai, Takashi
Highlights: We evaluated 86 patients with CSM using kinematic CT myelography and central motor conduction time, and how radiological parameters affect the severity of myelopathy. Exhibiting more severe upper limbs dysfunction was associated with severe spinal cord compression and large dynamic change of the spinal cord. Exhibiting more severe lower limbs dysfunction was associated with larger C2-7 SVA, larger cervical lordosis during flexion, severe spinal cord compression during flexion and extension and small C2-7 ROM neutral position to flexion. The key radiological factors associated with the more severe lower limb dysfunction than upper limb would be anterior spondylolisthesis during neck extension and neck stiffness during flexion. Abstract: Patients with cervical spondylotic myelopathy (CSM) often exhibit symptoms in clinical practice, particularly the elderly, whose lower extremity functions are more likely to deteriorate; however, the underlying mechanisms currently remain unclear. The present study aimed to elucidate the relationship between the neurological severity of CSM based on an electrophysiological examination and radiological findings. Eighty-six patients with CSM were examined using kinematic CT myelography. The cross-sectional area of the spinal cord and dynamic changes in the spinal cord were measured at the affected level. The central motor conduction time (CMCT) using transcranial magnetic stimulation was calculated as follows: motor evoked potential latency - (compound muscle action potential latency + F latency − 1)/2 (ms). A multiple logistic regression analysis was performed to identify the radiological parameters associated with severe lower limb dysfunction. CMCT in the upper limbs correlated with spinal cord compression during neck extension, while that in the lower limbs correlated with a larger C2-7 sagittal vertical axis, cervical lordosis, a small C2-7 range of motion (ROM), and spinal cord compression during neck flexion. In a multiple logistic regression analysis, significant risk factors specific for severe lower limb dysfunction were greater anterior spondylolisthesis during neck extension (P = 0.006, OR: 2.53, 95%CI: 1.13–2.07) and small C2-7 ROM in neutral to flexion (P = 0.035, OR: 0.67, 95%CI: 0.52–0.88). Imaging findings affect upper and lower extremity functions in specific manners. Cervical stiffness or anterior compression factors may be associated with the deterioration of lower limb function.